Free-floating car-sharing electrification and mode displacement: Travel time and usage patterns from 12 cities in Europe and the United States - Sprei, Frances; Habibi, Shiva; Englund, Cristofer; Pettersson, Stefan; Voronov, Alex; Wedlin, Johan (Transportation research. Part D, Transport and environment, 2019)
•Free-floating car sharing (FFCS) is studied through booking data in 12 cities.•Rental times are compared with travel times for alternative modes.•Rental times are often longer than biking times.•Public transport is often slower but the time gain with FFCS is not always that large.•Usage patterns differ between electric and conventional vehicles, but the spread is large. Free-floating car-sharing (FFCS) allows users to book a vehicle through their phone, use it and return it anywhere within a designated area in the city. FFCS has the potential to contribute to a transition to low-carbon mobility if the vehicles are electric, and if the usage does not displace active travel or public transport use. The aim of this paper is to study what travel time and usage patterns of the vehicles among the early adopters of the service reveal about these two issues. We base our analysis on a dataset containing rentals from 2014 to 2017, for 12 cities in Europe and the United States. For seven of these cities, we have collected travel times for equivalent trips with walking, biking, public transport and private car. FFCS services are mainly used for shorter trips with a median rental time of 27 min and actual driving time closer to 15 min. When comparing FFCS with other transport modes, we find that rental times are generally shorter than the equivalent walking time but longer than cycling. For public transport, the picture is mixed: for some trips there is no major time gain from taking FFCS, for others it could be up to 30 min. For electric FFCS vehicles rental time is shorter and the number of rentals per car and day are slightly fewer compared to conventional vehicles. Still, evidence from cities with an only electric fleet show that these services can be electrified and reach high levels of utilization.